Would teaching sustainable development business strategies shift students' mindsets? An Australian experience - Issa, Theodora; Issa, Tomayess; Chang, Vanessa (Common Ground Publishing, 2011)
The aim of this study is to examine students “Reactions towards sustainability and ‘Green IT’ following the completion of the postgraduate unit ITS6 in semester 2 2010. It is evident that emerging concept relating to the topic ‘Sustainability and Green IT’ are gaining momentum, having an increased importance for both practitioners and academics alike. This comes especially following the self-reflection by all parties following the Global Financial Crisis of 2008/2009 coupled with the ongoing change in climate. Both of these factors are having their negative ramifications on individuals, businesses, communities, and societies, urging them to question their involvement and any efforts that they might exert to avert or rather reduce the negative consequences experienced so far. Business schools were amongst those who have been blamed for economic, societal and environmental failures. Several of these business schools were and continue to be taking measures to rectify what might have been lack of concentration on ‘soft issues’ in business and management. Indeed, the idea behind the development of ITS6 unit was to enhance and improve students’ awareness of the roles information technology and information systems play in business, their impact, and that of business on all aspects of life including the environment.To assist students to achieve this unit’s outcomes, assessments were designed in a manner that would allow them to foster synthesis within their studies, thus developing, improving, and enhancing their learning and understanding. The assessments were three: three reflective accounts/journals, an oral presentation, and a written report. Through the preparation of their three reflective accounts/journals, students were able to reflect on their learning. This activity formed a major part of their overall unit assessment. This specific activity and being in three parts allowed proper monitoring of students’ developments and enhanced capabilities. This assessment was designed to offer students the experience to critically, creatively and reflectively, review and record key aspects and concepts. These experiences were coupled with their thoughts about materials provided or located by them either through their ongoing readings of textbooks, journal articles or through their searches over the World Wide Web. Adopting this assessment at the postgraduate level while teaching ‘ITS6’ entailed two benefits. First, it allowed us to teach students how to analyse and synthesise the diverse types of information outlined in the sourced articles and publications.Second, as a result of their own readings, analyses, and syntheses, students were able to enhance their own learning in this unit, thus displaying a shift in their frames and understanding of the material presented to them and generated by them. As a result, this unit ultimately changed the students’ mindsets. For this study, the researchers collected the data through quantitative and qualitative techniques. This was done to lessen the shortcomings of each method when used on its own. This study provides a reflection on such activity, establishing a comparison to ascertain whether students have benefited from the material provided in this unit, and thus whether outcomes identified and attached to this unit were achieved. This study is a rather modest contribution to the ongoing debate as to whether students’ mindsets shift following exposure to material that they were almost unaware of, thus changing their mindsets and transforming them into advocates of sustainable development and its relationship with the IT industry.